PANDAWA LIMA: PERWUJUDAN NILAI-NILAI KARAKTER BANGSA - Purwadi (Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
Leather puppet or classical Javanese ‘wayang’ contains rich moral teaching practiced in human life. The current article aims at describing and analyzing Pandawa Lima characters reflecting five principal nation character values designed by the government. Content analysis is employed to study verbal expressions obtained from the narration of play scripts and ‘wayang kulit’ performance. The result of the study demonstrates that the characters of Pandawa reinforce five principal nation character values, namely (1) Puntadewa completely represents religious character values with sub-values of belief in God, being pious and absolutely obedient to God, care to others, and being harmonious with environment; (2) Werkudara fully represents character values of nationalism with sub-values of love to the homeland, spirit of nationality, devotion to the country, and pluralism; (3) Arjuna partly represents the character values of being independent with sub-values of lifelong learners, hardworkers, and being resilient; (4) Nakula partly represents the character values of working together with the sub-values of collaboration, helping each other, and doing things in a voluntary way; (5) Sadewa partly represents integrity character values with sub-values of being keen on the truth, moral commitment, responsibility, and respecting others.